Analysis of the Influence of Financial Literacy Levels on Financial Management and Micro Business Sustainability (Case Study on Micro Businesses in Bandar Lampung - Ghesna Larasati Sunatriyo (Green Publisher Indonesia, 2025)
This study analyzes the influence of financial literacy level on financial management and sustainability of micro businesses in Bandar Lampung. The research method used is qualitative with a case study approach. Primary data were obtained through questionnaires distributed to 137 respondents and in-depth interviews with 5 micro business actors. The results of the study show that the level of financial literacy of micro business actors in Bandar Lampung falls into the category of sufficient literacy, with an average score of 3.83. The findings reveal that financial literacy has a significant impact on business financial management, with an average score of 4.10, as reflected in the aspects of financial planning, recording, reporting, and control. Financial literacy also has a positive effect on business sustainability, with an average score of 3.72, where business actors who possess good financial understanding tend to engage in long-term planning and are able to make data-based strategic decisions. The results confirm the Resource-Based View theory, which posits that financial literacy is a strategic resource that can enhance the competitiveness and resilience of micro businesses in facing market challenges.